DENTAL AGE ESTIMATION IN A SAMPLE OF CHILDREN POPULATION FROM IASI COUNTY - Carmen Savin; Adriana Bălan; Laura Maria Gavrilă; Ana Sîrghe; Raksha Batajoo; Bogdan Dragomir (Romanian Society of Oral Rehabilitation, 2018)
Estimation of dental age in pediatric dentistry, orthodontics and forensic dentistry is a continuous challenge due to the fact that it is very important in assessing if the adult age was reached or not, in determining growth and somatic development. Aim. To assess the accuracy of dental age estimation by Demirjian and Nolla methods in a sample of Romanian children population. Materials and Methods. The study was carried on a number of 161 orthopantomographs of Romanian boys and girls of known chronological age. Dental age accuracy was estimated by calculating how close the estimated dental age was to the actual chronological age. Results and discussions. There was a strong correlation between chronological age and dental age calculated by Demirjian method; the same situation was found in the case of the dental age estimated by the Nolla method. Dental age prediction by Nolla method was more accurate than the one of Demirjian method in both genders in our micro-study. Conclusion. To improve accuracy of dental age estimation it is preferable to elaborate further specific curves and scores for the Romanian population that must be developed and tested, based on ethnicity.